2018
DOI: 10.1002/gcc.22684
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms shaping the mutational landscape of the FRA3B/FHIT‐deficient cancer genome

Abstract: Genome instability is an enabling characteristic of cancer that facilitates the acquisition of oncogenic mutations that drive tumorigenesis. Underlying much of the instability in cancer is DNA replication stress, which causes both chromosome structural changes and single base‐pair mutations. Common fragile sites are some of the earliest and most frequently altered loci in tumors. Notably, the fragile locus, FRA3B, lies within the fragile histidine triad (FHIT) gene, and consequently deletions within FHIT are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…It is conceivable that selection pressure for a higher grade of Kras activation may underlie sarcomagenesis, which is canceled once p53 is deleted, although underlying molecular mechanisms remain unknown. By analogy with the frequent deletion of the FRA3B common fragile site in multiple cancer types [39], we speculate the presence of putative fragile sites around the Kras locus that are predisposed to deletion, especially in cancers with Kras mutation – with high penetrance of deletion, the current model would provide a unique opportunity to verify this. Furthermore, consistent with the crucial roles of TGF‐β signaling in Kras ‐associated EMT [40], loss of Tgfbr2 directed the development of adenocarcinoma, but not sarcoma.…”
Section: Discussionmentioning
confidence: 81%
“…It is conceivable that selection pressure for a higher grade of Kras activation may underlie sarcomagenesis, which is canceled once p53 is deleted, although underlying molecular mechanisms remain unknown. By analogy with the frequent deletion of the FRA3B common fragile site in multiple cancer types [39], we speculate the presence of putative fragile sites around the Kras locus that are predisposed to deletion, especially in cancers with Kras mutation – with high penetrance of deletion, the current model would provide a unique opportunity to verify this. Furthermore, consistent with the crucial roles of TGF‐β signaling in Kras ‐associated EMT [40], loss of Tgfbr2 directed the development of adenocarcinoma, but not sarcoma.…”
Section: Discussionmentioning
confidence: 81%
“…It has been reported that Signature 5 is driven by the loss of FHIT gene [ 41 ]. Depletion of FHIT causes replication stress-induced DNA double-strand breaks and defects in replication fork progression and prevents activation of DNA damage response [ 54 ]. It is likely that the majority of somatic mutations in plasma are likely due to the result of replication errors and lack of DNA damage responses.…”
Section: Discussionmentioning
confidence: 99%
“…FRA3B and FRA16D are the two most frequently affected CFS in human cancers, including breast, lung, colon, esophageal, and renal carcinomas (Durkin and Glover, 2007). FRA3B is located at 3p14.2 and overlaps with the 1.5 Mb-long Fragile Histidine Triad (FHIT) tumor suppressor gene, which is involved in nucleotide metabolism (Saldivar and Park, 2019). FRA3B instability is caused by a paucity of replication initiation events at the central region of this fragile site, as well as transcription-replication collisions due to extended transcription of the large FHIT gene (Helmrich et al, 2011;Letessier et al, 2011).…”
Section: Genomic Regions Susceptible To Replication Stressmentioning
confidence: 99%